COVID-19 Misinformation Detection in Indonesian Tweets using BERT - Fahmi Adi Nugraha; Dhomas Hatta Fudholi (Universitas Budi Darma, 2023)
The COVID-19 pandemic has seen a marked increase in the spread of misinformation throughout various media channels, most notably social media. This is particularly true of Indonesia where a combination of middling digital literacy and the slow speed of fact-checking contributes to the continued spread of misinformation. Many of the solutions proposed by other researchers to address this problem do not use transformers despite the existence of Indonesian language BERT models. Thus, in order to both provide a potential solution to the problem of misinformation as well as a baseline for future research we propose an IndoBERT-based model for detecting misinformation in Indonesian language Tweets. For model training, we use the